2009
DOI: 10.1002/chem.200802238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Highly Efficient Alkylated Pincer Thioimido–Palladium(II) Complex as the Active Catalyst in Negishi Coupling

Abstract: The induction period of Negishi coupling catalyzed by pincer thioamide-palladium complex 1 was investigated. A heterogeneous mechanism was excluded by kinetic studies and comparison with Negishi coupling reactions promoted by Pd(OAc)(2)/Bu(4)NBr (a palladium-nanoparticle system). Tetramer 2 was isolated from the reaction of 1 and organozinc reagents. Dissociation of complex 2 by PPh(3) was achieved, and the structure of resultant complex 8 was confirmed by X-ray diffraction analysis. A novel alkylated pincer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…For instance, Lei et al. employed a bis(thioamide)pyridine ligand to prepare a Pd II –SNS pincer complex . Its catalytic performance has been studied in the reaction between aryl iodides with alkylzinc derivatives under mild conditions (Scheme ).…”
Section: Cross‐coupling Reactionsmentioning
confidence: 99%
“…For instance, Lei et al. employed a bis(thioamide)pyridine ligand to prepare a Pd II –SNS pincer complex . Its catalytic performance has been studied in the reaction between aryl iodides with alkylzinc derivatives under mild conditions (Scheme ).…”
Section: Cross‐coupling Reactionsmentioning
confidence: 99%
“…At the low catalyst loading (0.1-0.5 mol%), both catalysts promoted the reactions at room temperature or even at 0 C and provided high turnover numbers up to 6,100,000 [52]. Additional experiments showed that an active catalyst was an alkylated adduct generated from the catalyst precursor and basic metal reagents under reaction conditions (Scheme 14) [53].…”
Section: Bis(thioamide) Pincer Compoundsmentioning
confidence: 97%
“…Yet another alternative tactic to supersede the β-hydride elimination pathway consists of using catalytic systems operating through a mechanism engaging a Pd(II)/Pd(IV) shuttle, as it has been suggested that reductive elimination from (diorgano)Pd(IV) is a fast process. Pincer thioimido-Pd(II) complexes such as 346 can readily promote the cross-coupling between aryl iodides and alkylzincs, with low catalyst loadings and at temperatures as low as −20 • C (Scheme 4.79) [250,251]. When secondary cycloalkylzincs such as 341 are used, levels of selectivity with regard to competing reduction are excellent.…”
Section: And the Analogous Sphosmentioning
confidence: 99%